Efektivitas Sistem Angkut Bahan Baku Tandan Buah Segar (TBS) Kelapa Sawit Untuk Peningkatan Mutu Buah di Kebun - Yoga, Tirta; Subagyo, Heru Santoso Hadi (Musamus University, 2022)
The purpose of this study was to analyze the factors that affect the transportation of FFB raw materials (Fresh Fruit Bunches) and to analyze the effectiveness of the FFB raw material transportation system implemented by PTPN V Kebun Tandun which affects the quality of FFB. Retrieval using key informant techniques on the part of the garden transportation unit. The data analysis method uses fishbone analysis and antrain analysis using QM software for Windows V4. Fishbone analysis method was analyzed to identify the limiting factors that affect the transportation of FFB, while queuing analysis was used to determine the effectiveness of the transportation system. The data used to analyze the queuing system are primary data and secondary data, namely customer arrival time data and service time data (server). The results showed that the factors that affect the transportation of FFB are method, material and environment. Queues at the weighing unit and transportation needs affect the increase in Free Fatty Acid (ALB) levels. At low daily production, the arrival rate of trucks per day is 5 trucks/hour with a queue length of 1 truck and a queue time of 4 minutes. At peak production, the arrival rate of trucks is 12 trucks/hour, the queue length is 22 trucks and the average queue time is 115 minutes.